TRANFORMASI SOSIAL KAMPUNG NAGA SEBAGAI DESTINASI WISATA BUDAYA DAN LINGKUNGAN (DENGAN PENDEKATAN KONSTRUKSI SOSIAL) - Arief Faizal Rachman (Jurnal Hospitality dan Pariwisata, 2017)
Cultural and environment tourism development in Kampung Naga constructed by the high demand of visitor that came to Kampung Naga. This is a social process that contested stakeholder, such as local community and tour operator. All this stakeholder had their own self interest, stated as the elemensof their social concept. Different value of elements between stakeholder created interest between them. The reseearch used descriptive explorative methodology to find out social transformation between stakeholder. The results of this research are local community of Kampung Naga open theirself on the dynamics of tourism there. Social transformation happened in Kampung Naga, both physical and function transformaion. Tour operator interest to visit more to Kampung Naga.. Nevertheless, culture and environment of Kampung Naga sustain till present time. Keywords: cultural tourism, stakeholder, social construction, tourism destination, social transformation